Investigation Into Different Wood Formation Mechanisms Between Angiosperm and Gymnosperm Tree Species at the Transcriptional and Post-transcriptional Level - Li, Hui; Chen, Guanghui; Pang, Hongying; Wang, Qiao; Dai, Xinren (Frontiers in Plant Science, 2021)
Enormous distinctions of the stem structure and cell types between gymnosperms and angiosperms tree species are expected to cause quite different wood physical and mechanical attributes, however, the molecular mechanisms underlying the differing wood morphology are still unclear. In this study, we compared the transcriptomes obtained by RNA-Seq between Populus alba × P. glandulosa clone 84K, and Larix kaempferi (Lamb.) Carr trees. Available genome resource served as reference for P. alba × P. glandulosa and the Iso-Seq results of a three-tissues mixture (xylem, phloem, and leaf) were used as the reference for L. kaempferi to compare the xylem-specifically expressed genes and their alternative splicing model. Through screening, we obtained 13 907 xylem-specifically expressed genes (5 954 up-regulated, 7 953 down-regulated) in the xylem of P. alba × P. glandulosa, and 2 596 xylem-specifically expressed genes (1 648 up-regulated, 948 down-regulated) in the xylem of L. kaempferi. From the GO and KEGG analyses, some genes associated with two wood formation-related pathways, namely those for phenylpropanoid biosynthesis, and starch and sucrose metabolism, were successfully screened. Then the distributions and gene expression models between P. alba × P. glandulosa and L. kaempferi in those pathways were compared, which suggested differential wood formation processes between the angiosperm and gymnosperm trees. Furthermore, a Weight Gene Co-expression Network Analysis (WGCNA) for total xylem-specifically expressed genes in two species was conducted, from which wood formation-related modules were selected to build a co-expression network for the two tree species. The genes within this co-expression network showed different co-expression relationships between the angiosperm and gymnosperm woody species. Comparing the alternative splicing events for wood formation-related genes suggests a different post-transcriptional regulation process exists between the angiosperm and gymnosperm trees. Our research thus provides the foundation for the in-depth investigation of different wood formation mechanisms of angiosperm and gymnosperm species.